Aqueous Tear Deficiency Increases Conjunctival Interferon-γ (IFN-γ) Expression and Goblet Cell Loss - Pflugfelder, Stephen C.; De Paiva, Cintia S.; Moore, Quianta L.; Volpe, Eugene A.; Li, De-Quan; Gumus, Koray; Zaheer, Mahira L.; Corrales, Rosa M. (Investigative ophthalmology & visual science, 2015)
To investigate the hypothesis that increased interferon-γ (IFN-γ) expression is associated with conjunctival goblet cell loss in subjects with tear dysfunction. Goblet cell density (GCD) was measured in impression cytology from the temporal bulbar conjunctiva, and gene expression was measured in cytology samples from the nasal bulbar conjunctiva obtained from 68 subjects, including normal control, meibomian gland disease (MGD), non-Sjögren syndrome (non-SSATD)-, and Sjögren syndrome (SSATD)-associated aqueous tear deficiency. Gene expression was evaluated by real-time PCR. Tear meniscus height (TMH) was measured by optical coherence tomography. Fluorescein and lissamine green dye staining evaluated corneal and conjunctival disease, respectively. Between-group mean differences and correlation coefficients were calculated. Compared to control, IFN-γ expression was significantly higher in both ATD groups, and its receptor was higher in SSATD. Expression of IL-13 and its receptor was similar in all groups. Goblet cell density was lower in the SSATD group; expression of MUC5AC mucin was lower and cornified envelope precursor small proline-rich region (SPRR)-2G higher in both ATD groups. Interferon-γ transcript number was inversely correlated with GCD (r = -0.37, P < 0.04) and TMH (r = -0.37, P = 0.02), and directly correlated with lissamine green staining (r = 0.51, P < 0.001) and SPRR-2G expression (r = 0.32, P < 0.05). Interferon-γ expression in the conjunctiva was higher in aqueous deficiency and correlated with goblet cell loss and severity of conjunctival disease. These results support findings of animal and culture studies showing that IFN-γ reduces conjunctival goblet cell number and mucin production.